2010
DOI: 10.1016/j.jiph.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining poor practice in alcoholic gel hand rub technique in hospital workers

Abstract: These results demonstrate that an educational program can significantly improve the proper practices for using hand rub and hand washing compliance. This study has also demonstrated that wearing rings, bracelets, watches and long nails impair hand gel application but that wedding rings, long sleeves and varnished nails do not. The finding of that hand hygiene effectiveness increased with time even prior to training indicates that knowledge gained by staff trained early diffused into those who had not yet been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
1
15
1
7
Order By: Relevance
“…We found that recovery of potential pathogens was similar from HCP who used alcohol sanitizer versus soap and water, which is generally inconsistent with the findings of others as alcohol-based hand hygiene has been found to be more effective than antiseptic or plain soap [1]. Previous studies have shown reduced hand hygiene compliance among physicians compared to nurses and among men compared to women [9,10]. In this study, men were more likely to have hand carriage of potential pathogens, and we speculate that this finding reflected that more time had elapsed since their last episode of hand hygiene when compared to women.…”
Section: Discussioncontrasting
confidence: 64%
“…We found that recovery of potential pathogens was similar from HCP who used alcohol sanitizer versus soap and water, which is generally inconsistent with the findings of others as alcohol-based hand hygiene has been found to be more effective than antiseptic or plain soap [1]. Previous studies have shown reduced hand hygiene compliance among physicians compared to nurses and among men compared to women [9,10]. In this study, men were more likely to have hand carriage of potential pathogens, and we speculate that this finding reflected that more time had elapsed since their last episode of hand hygiene when compared to women.…”
Section: Discussioncontrasting
confidence: 64%
“…Maintaining short fingernails decreases the risk of puncturing gloves, harboring pathogens under the nails, impeding proper hand hygiene, and possibly injuring patients. Studies have demonstrated that both artificial nails and nail extenders contribute to contamination of the hands and have led to outbreaks of infection 2‐9 . The hospital where Nurse S is employed allows personnel to wear nail polish, as long as it is freshly applied and not chipped.…”
Section: Key Takeaways Discussionmentioning
confidence: 99%
“…Recently, studies have looked at the social and behavioural contexts affecting hand hygiene practices. However, much still needs to be learned (25)(26)(27)(28)(29)(30)(31)(32). There are no previous studies on hand hygiene determinants in the Egyptian health-care setting.…”
Section: Introductionmentioning
confidence: 99%